العلاقات العامة الرقمية وصناعة الصورة الذهنية للمنظمات الحديثة قراءة تحليلية في ظل البيئة الافتراضية - قادم, جميلة (جامعة الوادي - University of Eloued, 2022)
تعد العلاقات العامة الرقمية من أحدث المفاهيم في إدارة صورة وسمعة المنظمات، حيث تحقق التفاعل المباشر مع الجمهور تجاه المنظمات خاصة فيما يتعلق بتحسين الصورة الذهنية وبتعزيز هويتها. وتُعتبر إدارة الصورة الذهنية للمنظمة إحدى أهم وظائف العلاقات العامة، التي تهدف إلى بناء وتدعيم صورة ذهنية إيجابية عنها. سعت هذه الدراسة إلى التعرف للدور البارز الذي تقوم به العلاقات الرقمية في تشكيل صورة وسمعة المؤسسة. وخلصت الدراسة بأن تحسين الصورة الذهنية للمنظمة يستدعي إعادة النظر في الموروث السابق لكل من تسويق المحتوى الإتصالي واستراتيجيات إدارة الصورة الذهنية ، و التمكن من أساسيات التسويق الرقمي المعاصر. Abstract: Digital public relations is one of the latest concepts in the management of the image and reputation of organizations, it achieves direct interaction with the public towards issues of interest to organizations, especially with regard to improving the mental image. Managing the mental image of the organization is one of the most important functions of public relations, which mainly aims to build a positive mental image. this study seeks to identify the role played by digital relations in shaping the image of the institution. The results confirmed that the success of digital public relations in improving the mental image of organizations calls for reconsidering the previous legacy of each of the communication content marketing and strategies for managing the mental image of the organization, in addition to mastering the basics of digital marketing.
Digital public relations and the mental image industry for modern organizations: Analytical reading under the virtual environment
مقال
Keywords: العلاقات العامة الرقمية، الصورة الذهنية، أليات إدارة الصورة، البيئة الافتراضية ، المنظمات الحديثة; digital public relations, mental image, image management mechanisms, virtual environment, modern organizations